The art of bouncing back – patient perspective on living with cancer - Denvall, Verner Denvall (Socialmedicinsk tidskrift, 2022)
Avhandling av Ulrika Sandén (2021). (Diss). Lund: Lunds universitet, institutionen för designvetenskaper. E-post: ulrika.sanden@design.lth.se